Lampião da Esquina: homossexualidade e violência no Brasil (1978-1981) - Mariusso, Victor Hugo da Silva Gomes (2015)
Homosexuality built in the late nineteenth century as something to be fought, because it is a disease, a perversion of something sinful and dangerous to the current regulations (heteronormativity) still pervades in Brazilian society sexist, patriarchal, nuclear, phallic and homophobic, and which is capable of killing a homosexual approximately every 28 hours in the country. In this way we intend through this research to analyze the violence against homosexuals in the decline of the period of military dictatorship in Brazil, specifically the period of 1978-1981, through the Lampião da Esquina newspaper. Thus, analyze the gay press through this newspaper, which was the first homosexual periodical to circulate throughout the country. Also consider the period and its subjects through its pages, represented by Brazilian society at the time. Analyze how and which provided the emergence of a gay newspaper in the country, which makes it possible to analyze the mainstream press of the period, as well as the alternative press. In other words, a look at the period through the gay press, which makes it possible an analysis of homosexuality, violence and the press of the period.